The Implementation of Think-pair-share Strategy in Improving Grade XI Students’ Achievement in Reading Comprehension - Harisma, Rita; Niswa, Khairun (AIBPM Publisher, 2023)
The objective of this research is Classroom Action Research (CAR) was to discover the implementation of Cooperative Learning namely Think-Pair comprehension. Thirty-two students of Grade XI-Science 2 of State Senior High School (Sekolah Menengah Atas Negeri: SMAN) 4 Kisaran were taught Reading Comprehension using TPS strategy. The students were divided into sixteen pairs. The researcher was assisted by a collaborator. The data were obtained through observation, field notes, quiz, and questionnaire. This research was conducted by (1) giving reading comprehension test as preliminary study to find out the students’ achievement in reading comprehension, (2) designing a lesson plan, and (3) implementing the CAR in 3 cycles, each cycle consisted of 2 meetings. In Cycle 1, the result of the students’ mean score was x = 59; in Cycle 2 x= 69,7; and in Cycle 3 improved to x = 79,6. It had met the criteria of success, 75% of the students reached the score 70 or more.